Clinical Aspects of Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis With Severe Ocular Complications in Brazil - Wakamatsu, Tais Hitomi; dos Santos, Myrna Serapião; Barreiro, Telma Pereira; Sant'Anna, Ana Estela Besteti Pires Ponce; Murta, Fabíola; da Costa, Alexandre Xavier; Marculino, Leonardo Guedes C.; de Alcântara, Rafael Jorge Alves; de Farias, Charles Costa; Gomes, José Álvaro Pereira (Frontiers in Medicine, 2021)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are acute and potentially fatal inflammatory vesiculobullous reactions that affect the skin and mucous membranes, and which are most often triggered by particular medications and infections. In Brazil, the drugs most frequently associated with TEN and SJS include cold medicine such as dipyrone and NSAIDs, followed by carbamazepine, phenobarbital, penicillin, and allopurinol. Genetic variations have been found to increase the risk of SJS/TEN in response to triggering factors such as medications. The most closely associated genes found in Brazilian cold-medicine-related SJS/TEN patients with severe ocular complications are HLA-A*66:01 in those of mixed African and European ancestry and HLA-B*44:03 and HLA-C*12:03 in those of solely European ancestry. Our classification system for grading ocular surface complication severity in SJS/TEN patients revealed the most severe complications to be limbal stem cell deficiency and dry eye. Changes to the conjunctival flora have also been observed in SJS/TEN patients. Our group identified bacterial colonization in 95% of the eyes (55.5% of which were gram-positive cocci, 25.5% of which were gram-negative bacilli, and 19% of which were gram-positive bacilli). Several new treatment options in the acute and chronic ocular management of the SJS/TEN patients have been described. This article highlights some Brazilian institutions' contributions to ocular surface care in both the acute phase (including the use of amniotic membrane transplantation) and the chronic phase (such as eyelid margin and fornix reconstruction, minor salivary gland transplantation, amniotic membrane and limbal transplantation, scleral contact lenses, anti-angiogenic eyedrops for corneal neovascularization, ex-vivo cultivated limbal epithelium transplantation, conjunctival-limbal autografting, oral mucosa transplantation, and keratoprosthesis).